Teacher-Students’ Interaction in EFL Teaching: Analyzing Patterns of Classroom Interaction - Sophia Fithri Al-Munawwarah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Teacher-students’ interaction patterns in EFL teaching can be considered crucial to be investigated. It is due to the reason that interaction in English classroom may facilitate pupils in practicing the language skills they have learnt in a real context. In doing this, Classroom Discourse Analysis (CDA) can be an alternative way in order to seek the level of accuracy in portraying classroom activities. Dealing with this, the present study aimed at analyzing teacher-students’ interaction patterns that occurred in EFL classroom interaction. This was a descriptive qualitative study. The participants of this study were an English teacher at one vocational school students and 36 students of XII grade. In collecting the data, classroom observation was administered. The data then were transcribed and analyzed by using SMSLEFA (Synergetic Multilayered Students’ Learning Engagement Framework of Analysis) framework as a part of Classroom Discourse Analysis proposed by Suherdi (2010) and Berry’s Exchange System Network (ESN). The data revealed that both non-anomalous exchanges and anomalous exchanges occurred during the teaching and learning process, specifically there were 54 K-oriented exchanges, 36 S-oriented exchanges, and 6 A-oriented exchanges. In addition, Dk1-initiated patterns and Ds1-initiated patterns appeared as the dominant patterns in the corpus. The findings implied that the activities conducted by the teacher focused on checking students’ understanding about the text and developing students’ skill, particularly students’ reading skill and speaking skill. the result of this study can be utilize to investigate the effort that learners devote to the learning process that are linked to their achievement. Keywords: teacher-students’ interaction, Classroom Discourse Analysis, SMSLEFA